People's Republic of China-Hong Kong Special Administrative Region : Financial Sector Assessment Program-Insurance Core Principles-Detailed Assessment of Observance. (IMF Staff Country Reports; Country Report ;, 2014)
This Insurance Core Principles Detailed Assessment Report was prepared in the context of the Financial Sector Assessment Program for the People's Republic of China-Hong Kong Special Administrative Region (HKSAR). The report describes that the insurance penetration and density in HKSAR is among the top 10 in the world. Foreign-owned insurers are dominant in the HKSAR insurance sector, and account for about 72 percent of total assets as at end-2012. The long-term insurance industry is highly concentrated, while the market share of general insurance industry is more evenly distributed. All except one of the top-10 insurance groups are all foreign owned, with much larger consolidated operations compared to their operations in HKSAR. The Insurance Authority is responsible for regulating and supervising the insurance industry of the HKSAR. It is supported by the Office of the Commissioner of Insurance, a government department in the HKSAR. A self-regulatory system is used to supervise the conduct of business of intermediaries.